Pengaruh Stimulasi Pijat Bayi Terhadap Peningkatan Berat Badan Bayi pada Bayi Umur 1-6 Bulan: (di Wilayah Kerja Puskesmas Plandaan Kabupaten Jombang) - Puput Nur Rahayu; Umu Qonitun (Pusat Riset dan Inovasi Nasional, 2024)
Weight gain is one of the indicators of baby health that can be used as a benchmark for baby growth. One of the causes of weight problems is the baby's decreased appetite. There are still many babies whose weight gain is not optimal. This study aims to determine the effect of infant massage stimulation on infant weight gain in infants aged 1-6 months in the working area of the Plandaan Health Center, Jombang Regency.The research design used in this study is quantitative ''quasi-experimental'' using the ''non-equivalent control group'' research method. The population in this study of all babies aged 1-6 months who are in the working area of the Plandaan Health Center as many as 122 babies were selected by random sampling technique according to the criteria to get 32 babies aged 1-6 months, the variables in this study are infant massage stimulation and baby weight, the measuring tool in this study is a baby scale.The results of the study that there was a greater increase in weight in the intervention group than in the control group The results of the Wilcoxon Mann-Whitney test with a significance level of α = < 0.05 and the calculation was carried out with SPSS software version 26 for windows obtained Asymp value results. Sig. (2-tailed) = 0.010 which means that the smaller the ρ-value, the more significant the results of the study, so ρ = 0.010 < 0.05 then H1 is accepted. So that there is an effect of infant massage stimulation on infant weight gain in infants aged 1-6 months in the working area of the Plandaan Health Center, Jombang Regency.The conclusion of this study is that there is an effect of infant massage stimulation on weight gain in babies aged 1-6 months. This research is expected to be used as a source of information for midwifery education that there are